African philosophy in search of identity - Masolo, D. A. (African systems of thought., 1994)
A Kenyan philosopher surveys themes and debates in African philosophy over the last five decades. Masolo's purview includes Francophone and Anglophone philosophers in both the analytic and phenomenological traditions. -- Publisher description.